The use of hair as a long‐term indicator of low‐dose β2 agonist treatments in cattle: Implications for growth‐promoting purposes monitoring. Issue 6 (6th January 2019) - Liu, Jia; Tang, Chaohua; Long, Ruijun; Zhang, Kai; Han, Yunsheng; Zhao, Qingyu; Wang, Hongliang; Zhao, Fuzhong; Meng, Qingshi; Zhang, Junmin
Abstract: The objective of this study was to assess the feasibility of using hair as a long‐term indicator of cocktail (low‐dose β2 agonists) treatments in cattle. Six male Simmental cattle were treated with a mixture of low‐dose clenbuterol, ractopamine, and salbutamol at dosages of 5.3, 223.3, and 50.0 μg/kg, respectively. The trial lasted for 112 days and included 28 days of treatment and 84 days of withdrawal. Plasma and urine samples taken during the treatment period contained the highest residues, with maximum concentrations of clenbuterol, ractopamine, and salbutamol in plasma of 1.49 ng/mL (Day 21), 43.78 (Day 14) ng/mL, and 8.07 ng/mL (Day 7), respectively, and in urine of 62.40 ng/mL (Day 28), 3995.77 ng/mL (Day 28), and 503.72 ng/mL (Day 1), respectively. On day 42 of withdrawal, the residues of all three β2 agonists in plasma were below the limit of quantification (LOQ; 0.3 ng/mL for clenbuterol, and 0.5 ng/mL for ractopamine and salbutamol), and in urine samples were below or near the LOQ (the highest being ractopamine at 1.10 ng/mL). The highest concentrations of clenbuterol, ractopamine, and salbutamol in hair were 88.36, 1351.92, and 100.58 ng/g, respectively, on day 14 of withdrawal; and the residues were long‐lasting, with 7.64, 28.55, and 8.77 ng/g, respectively, on day 84 of withdrawal. The results of this study demonstrate that hair could be utilized as a long‐term indicator of the use of a combination of low‐dose β2 agonists in cattle, which could have implications for growth‐promoting purposes monitoring. Abstract : This study assessed the feasibility of using hair as a long‐term indicator of low‐dose β2 agonist treatments in cattle. On day 42 of withdrawal, the residues of the β2 agonists in plasma and urine were below or near the LOQ, while which in hair were more than 7.64 ng/g on day 84 of withdrawal. Hair could be utilized as a long‐term indicator of the use of a combination of low‐dose β2 agonists.